SPEAKING CHALLENGES THAT ENCOUNTER 2ND AND 3RD YEAR EFL UNIVERSITY STUDENTS - Feras Saleh A Al-Esaifer; Hisham Mohammed A. Alshareef (Premise: Journal of English Education and Applied Linguistics, 2018)
This research investigated the common problems and difficulties that face 2nd and 3rd year undergraduate students in developing their speaking skills. The qualitative approaches (interview and observation) were used as methods of collecting data of this study. Four classes were involved in the classroom observation, twenty students from this cohort and four teachers were interviewed. Some of the difficulties which were introduced in this study were related to the poor classroom conditions and methods that teachers employ in teaching speaking skills. Some other difficulties were related to pronunciation, including adding extra vowels and intonation and stress. Furthermore, there were other difficulties regarding the lack of vocabulary, which lead the students to avoid practicing their problems, have been provided in this study. The findings of this study are important as they represent the most influential factors which appear to be responsible for the problems of developing 2nd and 3rd year under- graduate students speaking skills. Recognition of the problems outlined in the first step of this study in order to supply appropriate solutions for overcoming these difficulties. In addition, these findings draw attention towards the importance of helping both the foreign language teachers and students to change their perspective about teaching and learning English speaking skills.